Virtual Communication Pattern Of Twitter Autobase Management (Study Of Sharing Real Life Things Media On @bertanyarl Account) - Muhd Ar. Imam Riauan; Zhafira Farras Salsabila (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Autobase raises the phenomenon of sending messages anonymously by using the help of Bots to send messages automatically via DM (direct messages) on Twitter. One of them is the @bertanyarl autobase, wihich allows its users to ask questions, discuss, or share things in real life which in its utilization and use cannot be separated from the help of the admin who manages and monitors the activities that occur in the @bertanyarl autobase. The purpose of this study was to determine the virtual communication pattern in the @bertanyarl autobase management as well as the supporting and inhibiting factors of the @bertanyarl Twitter autobasae management. This research uses a qualitative descriptive method, and the source of data obtained from five informants uses a purposive sampling technique. By using data collection techniques in the form of observation interviews and documentation, the results obtained are the managements virtual communication patterns carried out by the admin in the form of activities consisting of questions and answer about real life, open followback, MIXLR, and paid promotion, as well as efforts to maintain the security and comfort of the @bertanyarl autobase by creating rules or regulations and imposing sanctions. From each virtual communication, two different communication network pattern are found, known as the pattern of all channels and the pattern of the wheel. As well as the supporting factors found, namely the active Bot and sender features, the impediment is that Twitter frequently locks and suspends accounts.